Pengaruh Substitusi Sebagian Agregat Halus dengan Abu Limbah Kulit Sapi Terhadap Kuat Tekan Beton - Henda Riyana; Eko Walujodjati (Jurnal Konstruksi, 2022)
As an alternative to fine aggregate in the concrete mix, cowhide ash was used in this study. The percentage of fine aggregate substitute material used is 10%, 20%, and 30% by weight of fine aggregate. The purpose of this study is to determine the value of the compressive strength of concrete obtained from the results of testing the compressive strength of concrete. The research method used is experimental (experiment) carried out in the laboratory of the Garut Institute of Technology. The sample used is a cylindrical shape with a size of 10x20 cm for concrete samples with the addition of cowhide ash and 15x30 cm for normal concrete samples with a compressive strength plan of 20 MPa. Materials to be used as concrete mixtures are tested beforehand, including sieve analysis, specific gravity, water absorption, water content, silt content, organic content, and wear tests. After the mixing process is complete and the concrete dries at the age of 2 days, the concrete samples are soaked in water for 28 days. The test carried out was the compressive strength test at the age of 28 days of concrete. The average value obtained from each variation of the concrete mix is ​​that normal concrete has a compressive strength of 17.78 MPa, B1 has a compressive strength of 13.85 MPa, B2 has a compressive strength of 11.19 MPa, and B3 has a compressive strength of 10. 74 MPa.